Service provision in rural water supplies: analysis of four community-based systems in Colombia (2016)
Community management is the tendency to provide water to rural areas worldwide. Despite the diversity of rural communities and their water supplies, policies tend to be uniform, failing to be effective. Four rural water supplies in the Colombian Andes were studied combining quantitative and qualitative methods. Aspects of infrastructure, training of human resources, revenue collection, waterquality and post-construction support were studied. The study provides evidence on the need to design policies and programs that consider rural diversity to help communal water organizations to provide sustainable services.